Epithelial p38alpha controls immune cell recruitment in the colonic mucosa. - Young Jun Kang (Public Library of Science (PLoS), 2010)
Intestinal epithelial cells (IECs) compose the first barrier against microorganisms in the gastrointestinal tract. Although the NF-kappaB pathway in IECs was recently shown to be essential for epithelial integrity and intestinal immune homeostasis, the roles of other inflammatory signaling pathways in immune responses in IECs are still largely unknown. Here we show that p38alpha in IECs is critical for chemokine expression, subsequent immune cell recruitment into the intestinal mucosa, and clearance of the infected pathogen. Mice with p38alpha deletion in IECs suffer from a sustained bacterial burden after inoculation with Citrobacter rodentium. These animals are normal in epithelial integrity and immune cell function, but fail to recruit CD4(+) T cells into colonic mucosal lesions. The expression of chemokines in IECs is impaired, which appears to be responsible for the impaired T cell recruitment. Thus, p38alpha in IECs contributes to the host immune responses against enteric bacteria by the recruitment of immune cells.